Effects of canagliflozin on myocardial infarction: a post hoc analysis of the CANVAS programme and CREDENCE trial. Issue 4 (7th April 2021) - Yu, Jie; Li, Jingwei; Leaver, Phillip J; Arnott, Clare; Huffman, Mark D; Udell, Jacob A; Perkovic, Vlado; Mahaffey, Kenneth W; de Zeeuw, Dick; Fulcher, Greg; Matthews, David R; Shaw, Wayne; et al.
Abstract: Aims: Given the benefits of sodium glucose co-transporter 2 inhibition (SGLT2i) in protecting against heart failure in diabetic patients, we sought to explore the potential impact of SGLT2i on the clinical features of patients presenting with myocardial infarction (MI) through a post hoc analysis of CANVAS Programme and CREDENCE trial. Methods and results: Individuals with type 2 diabetes and history or high risk of cardiovascular disease (CANVAS Programme) or type 2 diabetes and chronic kidney disease (CREDENCE) were included. The intervention was canagliflozin 100 or 300 mg (combined in the analysis) or placebo. MI events were adjudicated as ST-elevation myocardial infarction (STEMI), non-STEMI, and type 1 MI or type 2 MI. A total of 421 first MI events in the CANVAS Programme and 178 first MI events in the CREDENCE trial were recorded (83 fatal, 128 STEMI, 431 non-STEMI, and 40 unknown). No benefit of canagliflozin compared with placebo on time to first MI event was observed [hazard ratio (HR) 0.89; 95% confidence interval (CI) 0.75, 1.05]. Canagliflozin was associated with lower risk for non-STEMI (HR 0.78; 95% CI 0.65, 0.95) but suggested a possible increase in STEMI (HR 1.55; 95% CI 1.06, 2.27), with no difference in risk of type 1 or type 2 MI. There was no change in fatal MI (HR 1.22, 95% CI 0.78, 1.93). Conclusion: Canagliflozin was not associated with a reduction in overall MI in the pooled CANVAS Programme and CREDENCE trial population. The possible differential effect on STEMI and Non-STEMI observed in the CANVAS cohort warrants further investigation. Trial registration: ClinicalTrials.gov identifiers: NCT01032629, NCT01989754, and NCT02065791. Graphical Abstract: